Coupled and decoupled legumes and cereals in prehistoric northern and southern China - He, Keyang; Yu, Xiaoshan; Shen, Caiming; Lu, Houyuan (Frontiers in Plant Science, 2022)
Legumes and cereals, which provide different nutrients, are cultivated as coupled crops in most centers of plant domestication worldwide. However, as the only legume domesticated in China, the spatio-temporal distribution of soybeans and its status in the millet- and rice-based agricultural system of the Neolithic and Bronze Ages remains elusive. Here, archaeobotanical evidence of soybeans (n=254), millet (n=462), rice (n=482), and zooarchaeological evidence of fish (n=137) were synthesized to elucidate the phenomenon of coupled or decoupled cereals and legumes in prehistoric China. During the Neolithic and Bronze Ages, soybeans was mostly confined to northern China and rarely found in southern China, serving as a companion to millet. In contrast, fish remains have been widely found in southern China, indicating a continuous reliance on fish as a staple food besides rice. Thus, an antipodal pattern of millet-soybeans and rice-fish agricultural systems may have been established in northern and southern China since the late Yangshao period (6000–5000 cal BP) respectively. These two agricultural systems were not only complementary in terms of diet, but they also exhibited positive interactions and feedback in the coculture system. Consequently, these two systems enabled the sustainable intensification of agriculture and served as the basis for the emergence of complex societies and early states in the Yellow and Yangtze Rivers.